(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
The history of the criminal jurisdiction of the Judiciary of La Pampa and the impact of social actors in their transformation, are issues that almost no academic studies at the provincial level. Indeed, through a legislative compilation made, which began in 1884 and lasted until 2016, it was to make a historical reconstruction of the evolution of the provincial criminal courts; in turn, each of the structural and procedural changes that occurred over the years analyzed were related and contrasted with provincial, national and international historical events, so try to arrive at an explanation regarding the reasons why they were thereby giving rise. In this way in the analysis quantitative changes were noted according to the structural increase immunity itself, and qualitative, that were intended to ensure efficient and actual response in key access to justice; recognition and respect of rights and constitutional guarantees and conventional; due process both defendants as victims; and, ultimately, greater efficiency in managing the conflict. This article constitutes the first part of the work carried out and comprises from the territorial stage until the National Territory of La Pampa was transformed into an autonomous province.